International Conference on Transportation and Development 2020 Transportation Safety - Zhang (American Society of Civil Engineers, 2020)
This collection contains 34 peer-reviewed papers on transportation safety presented at the International Conference on Transportation and Development 2020, held in Seattle, Washington, May 26-29, 2020.